1992
DOI: 10.1007/bf01819667
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of blood flow in the cerebral cortex of normal subjects during head-up postural change

Abstract: Regional cerebral blood flow was measured in 21 normotensive subjects during supine rest and during head-up tilt to 70 degrees. The results showed significant and consistent regional cerebral blood flow changes in the frontal areas with lower relative flow distribution values (percentage of mean flow) during head-up tilt than during supine rest. The lower frontal flow distribution values during tilt were not related to habituation, to repeated measurements, or to the estimated level of arterial CO2 which was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
2
18
2
Order By: Relevance
“…However, a recent study using PET in normal subjects revealed that rCBF values were increased in the cerebellar vermis and remained unchanged in the cerebellar hemispheres during the upright test, being in concordance with the notion that the cerebellar vermis is a neural substrate for controlling voluntary upright posture, and the use of the cerebellar hemisphere as a reference ROI seems to be validated [25]. In normal subjects, rCBF value measured by the xenon-133 inhalation method has been reported to decrease mildly in the frontal area during a head-up tilt [34]. However, in the present study, the CBF ratio in the frontal ROI was unchanged after rising in the lacunar infarction or control group.…”
Section: Discussionsupporting
confidence: 65%
“…However, a recent study using PET in normal subjects revealed that rCBF values were increased in the cerebellar vermis and remained unchanged in the cerebellar hemispheres during the upright test, being in concordance with the notion that the cerebellar vermis is a neural substrate for controlling voluntary upright posture, and the use of the cerebellar hemisphere as a reference ROI seems to be validated [25]. In normal subjects, rCBF value measured by the xenon-133 inhalation method has been reported to decrease mildly in the frontal area during a head-up tilt [34]. However, in the present study, the CBF ratio in the frontal ROI was unchanged after rising in the lacunar infarction or control group.…”
Section: Discussionsupporting
confidence: 65%
“…Due to similar decreases in PET CO 2 during orthostatic stress between sexes (as observed by Ref. 68) and greater reactivity to CO 2 in women, our primary hypothesis is that there will be a greater reduction in cerebral blood flow in upright postures in young women compared with young men. Furthermore, CO 2 reactivity decreases with age in women to a level equal with that of age-matched men (28).…”
mentioning
confidence: 64%
“…A relatively high fre quency of syncopal attacks has been reported in Pick's disease and therefore our observations of low mean blood pressure and a tendency to orthostatic blood pressure drop in FLD may be of special interest [24]. Neurological symptoms such as fascicular twitchings, muscular wast ing, dysarthria, dysphagia and extrapyramidal signs may develop in patients with FLD as also described in Pick's disease.…”
mentioning
confidence: 69%